Hydraena (s. str.) emineae sp. n. from Antalya, southern Turkey (Coleoptera: Hydraenidae) - Jäch, Manfred A.; Kasapoglu, Ahmet (Zootaxa, 2006)
Hydraena (s. str.) emineae Jäch & Kasapo™lu, sp. n. from Antalya, southern Turkey is described. The new species is tentatively assigned to the H. (s. str.) eichleri d’Orchymont species complex.